Reviews (Modern theology, 1988)
Book reviewed in this article: On Human Dignity: Political Theology and Ethics by Jürgen Moltmann Nineteenth Century Religious Thought in the West Edited by Ninian Smart, John Clayton, Patrick Sherry and Steven Katz Theological Dialogue between Orthodox and Reformed Churches Edited by T. F. Torrance A Black Theology of Liberation by James H. Cone Theology and Religious Pluralism: the Challenge of Other Religions by Gavin D'Costa Theology and the Problem of Evil by Kenneth Surin